Antibody response after COVID‐19 vaccination in intravenous immunoglobulin‐treated immune neuropathies. (8th August 2022) - Svačina, Martin K. R.; Meißner, Anika; Schweitzer, Finja; Ladwig, Anne; Sprenger‐Svačina, Alina; Klein, Ines; Wüstenberg, Hauke; Kohle, Felix; Schneider, Christian; Grether, Nicolai B.; Wunderlich, Gilbert; Fink, Gereon R.; et al.
Abstract: Background and purpose: This study assessed the prevalence of anti‐SARS‐CoV‐2 antibodies in therapeutic immunoglobulin and their impact on serological response to COVID‐19 mRNA vaccine in patients with intravenous immunoglobulin (IVIg)‐treated chronic immune neuropathies. Methods: Forty‐six samples of different brands or lots of IVIg or subcutaneous IgG were analyzed for anti‐SARS‐CoV‐2 IgG using enzyme‐linked immunosorbent assay and chemiluminescent microparticle immunoassay. Blood sera from 16 patients with immune neuropathies were prospectively analyzed for anti‐SARS‐CoV‐2 IgA, IgG, and IgM before and 1 week after IVIg infusion subsequent to consecutive COVID‐19 mRNA vaccine doses and after 12 weeks. These were compared to 42 healthy subjects. Results: Twenty‐four (52%) therapeutic immunoglobulin samples contained anti‐SARS‐CoV‐2 IgG. All patients with immune neuropathies (mean age = 65 ± 16 years, 25% female) were positive for anti‐SARS‐CoV‐2 IgG after COVID‐19 vaccination. Anti‐SARS‐CoV‐2 IgA titers significantly decreased 12–14 weeks after vaccination ( p  = 0.02), whereas IgG titers remained stable ( p  = 0.2). IVIg did not significantly reduce intraindividual anti‐SARS‐CoV‐2 IgA/IgG serum titers in immune neuropathies ( p  = 0.69). IVIg‐derived anti‐SARS‐CoV‐2 IgG did not alter serum anti‐SARS‐CoV‐2 IgG decrease after IVIg administration ( p  = 0.67). Conclusions: Our study indicates that IVIg does not impair the antibody response to COVID‐19 mRNA vaccine in a short‐term observation, when administered a minimum of 2 weeks after each vaccine dose. The infusion of current IVIg preparations that contain anti‐SARS‐CoV‐2 IgG does not significantly alter serum anti‐SARS‐CoV‐2 IgG titers. Abstract : This study assessed the prevalence of anti‐SARS‐CoV‐2 antibodies in therapeutic immunoglobulin and their impact on serological response to COVID‐19 mRNA vaccine in patients with intravenous immunoglobulin (IVIg)‐dependent chronic immune neuropathies. IVIg did not impair the antibody response to COVID‐19 mRNA vaccine when administered a minimum of 2 weeks after each vaccine dose. The infusion of current IVIg preparations that contain anti‐SARS‐CoV‐2 IgG did not significantly alter serum anti‐SARS‐CoV‐2 IgG titers.